A survey for citrus psorosis-associated virus in a citrus collection of Southern Italy - Djelouah K.; D'Onghia A.M. (Proceedings of the Mediterranean network on certification of citrus. 1995-1997, 1998)
The evaluation of the presence of CtRSV-Psorosis in a international citrus collection, previously indexed for psorosis, held at the Mediterranean Agronomic Institute of Valenzano (BA) and at the Dipartimento di Protezione delle Piante dalle Malattie, Università di Bari (Italy) (DPPM-UBA) was carried out using a DAS-ELISA kit produced at the Istituto di Fitovirologia Applicata (IFA)-CNR Torino (Italy) (Garcia et al., 1997). CtRSV-psorosis was widespread in most of the citrus varieties. ELISA confirmed the results obtained by indexing, with one exception of a local clementine cv. 'Fedele'. In two 'Navelina' samples ELISA was more sensitive than indexing in detecting the virus. The reliability and sensitivity of ELISA test can represent an important step toward routine serological indexing of this virus and eventual certification.
Round Table on: Citrus Virus and Virus-like Diseases and Certification: State of the Art, 1995/07/21, Bari (Italy)